DRD2 activation inhibits choroidal neovascularization in patients with Parkinson’s disease and age-related macular degeneration - Mathis, Thibaud; Baudin, Florian; Mariet, Anne-Sophie; Augustin, Sébastien; Bricout, Marion; Przegralek, Lauriane; Roubeix, Christophe; Benzenine, Éric; Blot, Guillaume; Nous, Caroline; Kodjikian, Laurent; Mauget-Faÿsse, Martine; et al. (The Journal of Clinical Investigation, 2024)
Neovascular age-related macular degeneration (nAMD) remains a major cause of visual impairment and puts considerable burden on patients and health care systems. l-DOPA–treated Parkinson’s disease (PD) patients have been shown to be partially protected from nAMD, but the mechanism remains unknown. Using murine models that combine 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine–induced (MPTP-induced) PD and laser-induced nAMD with standard PD treatment of l-DOPA/DOPA-decarboxylase inhibitor or specific dopamine receptor inhibitors, we here demonstrate that l-DOPA treatment–induced increase of dopamine-mediated dopamine receptor D2 (DRD2) signaling inhibits choroidal neovascularization independently of MPTP-associated nigrostriatal pathway lesion. Analyzing a retrospective cohort of more than 200,000 patients with nAMD receiving anti-VEGF treatment from the French nationwide insurance database, we show that DRD2 agonist–treated PD patients have a significantly delayed age of onset of nAMD and reduced need for anti-VEGF therapies, similar to the effects of the l-DOPA treatment. While providing a mechanistic explanation for an intriguing epidemiological observation, our findings suggest that systemic DRD2 agonists might constitute an adjuvant therapy to delay and reduce the need for anti-VEGF therapy in patients with nAMD.